Locke on attention. Issue 3 (4th May 2017) - Stuart, Matthew
ABSTRACT: Locke's remarks about attention have not received a great deal of attention from commentators. In Section 1, I make the case that attention plays an important role in his philosophy. In Section 2, I describe and discuss five Lockean claims about attention. In Section 3, I explore Locke's views about attention in relation to his account of sense perception. He thinks that we attend to objects by attending to ideas, and I argue that he treats sensory ideas as transparent in a particular sense. In Section 4, I raise the worry that some of Locke's remarks about attention seem at odds with his doctrine of the transparency of the mind. I offer two ways of resolving the problem, and suggest that they are parts of a single story.